Human IL-6-Producing B Cells Promote the Differentiation of Monocytes Toward an Anti-Inflammatory CD16⁺CD163⁺CD206⁺PD-L1⁺ Phenotype in Tuberculosis - Bénard, Alan; Balboa, Luciana; Caouaille, Maxime; Ravon-Katossky, Lea; Meunier, Etienne; Fillatreau, Simon; Sasiain, Maria Del Carmen; Neyrolles, Olivier; Hudrisier, Denis (European Journal of Immunology, 2025)
The polarization of the monocyte/macrophage compartment toward an anti-inflammatory profile is considered detrimental in tuberculosis (TB), but the factors controlling M2 polarization in this context are still poorly understood. Here, we found that B cells promote the differentiation of human monocytes toward an M2-like activation program through a process primarily dependent on IL-6 and the activation of STAT3 signaling in monocytes. This confers monocytes with immunomodulatory properties characterized by a reduced ability to produce proinflammatory cytokines and to stimulate IFNγ secretion by allogeneic T cells. Our findings were validated using B cells from TB patients, which constitutively produce high levels of IL-6, underscoring the clinical relevance of our experimental observations. Collectively, our results indicate that human B-cell-derived IL-6 might impair TB immunity by driving monocyte polarization toward an anti-inflammatory phenotype.
CRIS-Team Scopus Importer:2025-05-09